Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Halal Fashion - Tsania, Zukhrufa Hizballah; Muiz, Aris Nurul (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2025)
Halal fashion is one of the halal sectors that is currently very promising. Considering that the majority of modern Indonesian Muslims prefer to wear clothes that cover their private parts. Apart from being a representation of modern trends, the term